Improving Indonesian Librarian Competence Through System Benchmarking and Librarian Competency Certification Mechanism in the Philippines - Makarim, Luthfiati (Palimpsest: Jurnal Ilmu Informasi dan Perpustakaan, 2022)
This descriptive research describes the benchmark between the Philippine librarian certification system and mechanism with Indonesia librarian certification system and mechanism. The data is derived from a deep interview with a Philippine senior librarian who is also a member board of the PRC. Eight important variables are significant to be conducted in further research. The result should be followed up by the National Library of Indonesia together with the librarian association and other relevant stakeholders.